2012
DOI: 10.1007/s12663-012-0425-z
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Prevalence of Maxillofacial Fractures in Rural Children of Central Maharashtra, India. A Retrospective Study

Abstract: The aim of this study was to review the pattern and prevalence of maxillofacial fractures occurring in rural children, at Rural Dental College and Hospital, Loni, Central Maharashtra, India. A retrospective analysis of patient records and radiographs was conducted during the 5 year period between January 2005 and December 2010. Data were identified and analysed based on age group, gender and anatomic site. During the 5 year period, 156 patients with 163 maxillofacial fractures were reviewed, males formed 70 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
7
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
7
7
2
2
Order By: Relevance
“…Our findings showed that the mandible was the most involved bone (47.1%) followed by nasal bone fractures(43.9%), results that are in agreement with those reported by other authors ( 8 , 13 , 16 , 27 , 34 , 47 , 48 ). Zandi et al , Hussain et al ., showed that nasal bone fractures were the most prevalent type of trauma ( 3 , 18 , 45 ) which were the second most prevalent maxillofacial fracture in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that the mandible was the most involved bone (47.1%) followed by nasal bone fractures(43.9%), results that are in agreement with those reported by other authors ( 8 , 13 , 16 , 27 , 34 , 47 , 48 ). Zandi et al , Hussain et al ., showed that nasal bone fractures were the most prevalent type of trauma ( 3 , 18 , 45 ) which were the second most prevalent maxillofacial fracture in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that the mandible was the most involved bone (58.8%), consistent with other studies ( 5 , 10 , 12 , 17 , 31 , 32 , 39 , 50 ).…”
Section: Discussionsupporting
confidence: 93%
“…During 2 years, from January 2015 to December 2016, 502 patients were treated by the oral and maxillofacial surgery staff and residents in our department. In our study, the patient-to-year ratio was higher than what has been reported in most investigations into the prevalence of maxillofacial fractures in Iran ( 5 , 16 , 18 - 20 , 22 , 28 , 36 ), Italy ( 37 ), India ( 32 , 33 , 38 ), Brazil ( 4 , 39 , 40 ), Netherlands ( 41 ) and Serbia ( 42 ).…”
Section: Discussioncontrasting
confidence: 74%
“…Studies have shown that the peak incidences of maxillofacial fractures in rural children were found to be between the ages of 10 and 15 years. [ 10 11 ] However, in the present study, the age group most frequently involved in ZMCF was found to be 21–30 years (43.5%) followed by 11–20 years (28.8%). This may be attributed to the fact that individuals in the third decade of life are more physically active in Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 66%
“…This is in accordance with a study from an Indian community where most cases were diagnosed in August. [ 10 ] This was however different from those reported in an country in Arab where the peak incidence reported was in January followed by May. [ 9 ] This may be explained by the fact that August is the summer holiday at school and universities in Saudi Arabia and supported by the finding that the highest age group diagnosed with fractures are seen between 20 and 30 years.…”
Section: Discussionmentioning
confidence: 74%